Implementation of Pedagogy and Andragogy in Training Strategies to Enhance Vocational High School Teachers' Competence - Siti Maspupah; Babang Robandi; Mustofa Kamil; Elih Sudiapermana; Asep Saepudin; Iip Saripah (STAI Miftahul Ula Nganjuk, 2023)
This study aims to analyze the implementation of pedagogy and andragogy in training strategies to improve the competence of vocational/vocational teacher teachers. The method used in this study is a qualitative descriptive method with a case study approach. Data was collected through interviews, observation, and document study. The study results show that implementing pedagogy and andragogy in training strategies can improve the competence of vocational/vocational teacher teachers. Pedagogy is used for training novice teachers and andragogy is used for training experienced teachers. The training strategies carried out include: (1) developing curriculum, (2) developing training materials, (3) using information and communication technology, (4) developing learning strategies, and (5) evaluating and assessing training results. This is contained in several sections that are published, namely, implementation, strategy, inhibiting factors, and benefits of training.